Music and Basic Skills. Competence in autonomy and personal initiative (1/3) (Journal of Parents and Teachers, 2013)
First article from a series of 3 on “Music and Core Competences”. This article presents a proposal based on learning different skills in the classroom with the help of the music. The main objective is the Competence in Autonomy and Personal Initiative and, as an introductory article, justifies the approach taken. It is also a reflection of the competences and their relation with music. Finally, it provides some activities to do in the classroom.
Keywords: Music; Core Competences; Values; education and centerfold